2009
DOI: 10.1111/j.1468-2982.2009.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-craniotomy headache: A proposed revision of IHS diagnostic criteria

Abstract: Seventy-nine patients with intracranial aneurysms were evaluated in the presurgical period, and followed up to 6 months after surgery. We compare patients who fulfilled with those that did not post-craniotomy headache (PCH) diagnostic criteria, according to the International Classification of Headache Disorders. Semistructured interviews, headache diaries, Short Form-36 and McGill Pain Questionnaire were used. Seventy-two patients (91%) had headaches during the follow-up period. The incidence of PCH according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
(49 reference statements)
2
27
0
Order By: Relevance
“…There is a significant change in the headache pattern after craniotomy, in comparison with these patients' previous headaches . There is a significant increase in the frequency of headaches after surgery, and the majority of patients started to have headaches on the same side as and at the site of the surgery …”
Section: Characteristics Of Pchmentioning
confidence: 95%
See 2 more Smart Citations
“…There is a significant change in the headache pattern after craniotomy, in comparison with these patients' previous headaches . There is a significant increase in the frequency of headaches after surgery, and the majority of patients started to have headaches on the same side as and at the site of the surgery …”
Section: Characteristics Of Pchmentioning
confidence: 95%
“…Using the definition of PCH from the ICHD‐2, which is more restrictive than ICHD‐3, incidence of PCH was found to be 40% to 54.9%, acute PCH 10.7%, and chronic PCH 24% to 29.3% . Using ICHD‐3, the incidence of PCH was found to be 60% …”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Our contribution in the study of secondary types of headache is worthy of mention. Several articles have been published by Brazilian authors on headache possibly caused by an intracranial aneurysm . Krymchantowski described the clinical characteristics of the headache triggered by a policeman's helmet.…”
Section: Publications In Headache Medicinementioning
confidence: 99%
“…Several articles have been published by Brazilian authors on headache possibly caused by an intracranial aneurysm. 51,[282][283][284][285][286] Krymchantowski 287 described the clinical characteristics of the headache triggered by a policeman's helmet. In this connection, our group showed that the use of a ponytail by a woman more easily triggers a headache attack in migraineurs.…”
Section: Publications In Headache Medicinementioning
confidence: 99%